STRUKUR DAN NILAI MORAL CERPEN “KEADILAN” KARYA PUTU WIJAYA - Ayu Ajeng Agustina; Maulina Agustin; Yusep Ahmadi F (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This study refers to determine the structural elements and moral values in the short story “ Keadilan” by Putu Wijaya. This research can be useful for readers and can improve the ability to analyze the structural elements contained in the short research is qualitative descriptive. Source of data taken from the newspaper Jawa Pos October 07 2012. The data were analyzed by the structuralist approach, that is analyzing and interpreting the structural elements (intrinsic) in the short story. The results of the analysis found the elements of structure in the short story in the from of theme, plot, figure, background, the point of view, language style, conflict and elements it is unity to build a short story so that the work of literature. In addition, moral values are also found. Moral value are also found. Moral value is a value associated with good-bad, ethical and good character. That is the behavior shown by the character in the story.